THE EFFECT OF PRE-GERMINATION TREATMENTS ON THE QUALITY OF PLANT LOCUST (HYMENAEA COURBARIL) - Flores-Pacheco, J.A; Ramírez-James, M; Gutiérrez-Rugama, A; Flores-Pacheco, C.J; Alemán, Y (Nexo Revista Científica, 2017)
This research has evaluated the effect of five pre-germination treatments on the quality and structure of plant locust (Hymenaea courbaril) due to the high variability in the germination and emergency tillage. Five treatments were evaluated by measuring the rate of Germanization and emergency speed; quality parameters (height and diameter) together with biomass (fresh and dry weight) of seedlings, bringing the Dickson quality index were estimated. Each treatment group contained 50 replicates for 250 plants in the experiment. The data were processed with statistical SPSS V.22.0: variance, standard deviation, variance analysis, obtaining statistical tests of binary correlations, repeated measures analysis and analysis of variance (ANOVA), intra and inter groups, 95% (P-valor 0.05) of confidence. The results show differences between treatments three (hydration) and four (mechanical scarification) regarding treatment one (thermal) and two (chemical) where no statistically significant difference. Treatment five (witness) has less statistical difference with all other evaluated. These same data for determining a positive effect between application of pre germination treatments and increased seedling quality of 93.0%, this translates to a greater chance of survival of the plant to be transplanted in the field. It is tested combination treatments one and three.